PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI MIPA SMAN 14 PADANG - Fitri Anisa Wardani (Departemen Matematika, 2022)
Mathematical problem solving ability is one aspect that has an important role and becomes one of the goals that must be achieved by students in learning mathematics. However, in reality at SMAN 14 Padang showed that students' mathematical problem solving ability is still low. One of the learning models that can be applied to improve students' mathematical problem solving ability is Problem Based Learning (PBL). The purpose of this research is determine the mathematical problem solving ability of students who study with the Problem Based Learning model and compare it with direct learning in class XI MIPA SMAN 14 Padang. The type of research is a quasi-experimental with a static group comparison design. The population is students of class XI MIPA SMAN 14 Padang with a sample class XI MIPA 1 even absent as an experimental class and XI MIPA 6 even absent as a control class. The instrument of this research is in the form of a mathematical problem solving ability test. Based on the results of data analysis, using the t-test, obtained the P-value of 0.002. This shows the P-value , then is rejected. This means that the mathematical problem solving ability of students who study using the Problem Based Learning model is better than the mathematical problem solving abilities of students who learn using the direct learning model in class XI MIPA SMAN 14 Padang. Keywords – Learning Models, Problem Based Learning, Problem Solving